Is a joint moment-based cost function associated with preferred cycling cadence? - Marsh, A. P.; Martin, P. E.; Sanderson, D. J. (Journal of Biomechanics, 2000)
Eight experienced male cyclists (C), eight well-trained male runners (R), and eight less-trained male noncyclists (LT) were tested under multiple cadence and power output conditions to determine: (1) if the cadence at which lower extremity net joint moments are minimized (cost function cadence) was associated with preferred pedaling cadence (PC), (2) if the cost function cadence increased with increases in power output, and (3) if the association is generalizable across groups differing in cycling experience and aerobic power. Net joint moments at the hip, knee, and ankle were computed from video records and pedal reaction force data using 2-D inverse dynamics. The sum of the average absolute hip, knee, and ankle joint moments defined a cost function at each power output and cadence and provided the basis for prediction of the cadence which minimized net joint moments for each subject at each power output. The cost function cadence was not statistically different from the PC at each power output in all groups. As power output reased, however, the cost function cadence increased for all three subject groups (86 rpm at 100 W, 93 rpm at 150 W, 98 rpm at 200 W, and 96 rpm at 250 W). PC showed little change (R) or a modest decline (C, LT) with increasing power output. Based upon the similarity in the mean data but different trends in the cost function cadence and PC in response to changes in power output as well as the lack of significant correlations between these two variables, it was concluded that minimizing net joint moments is a factor modestly associated with preferred cadence selection.